Coating agent and method for manufacturing steel material using the same
Patent Information
- Application Number
- CN202580024229.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-04-05
- Filing Date
- 2025-04-04
- Publication Date
- 2026-10-30
AI Technical Summary
脱碳层降低钢材表层的强度
[0017]本公开的涂布剂即使在高温下加热钢材也能够抑制钢材表层的脱碳。本公开的钢材的制造方法能够制造脱碳得到抑制的钢材。
Smart Images

Figure FT_1 
Figure SMS_1 
Figure SMS_2
Abstract
Description
TECHNICAL FIELD
[0001] The present disclosure relates to a coating agent and a method for manufacturing steel material using the same. BACKGROUND
[0002] Steel material is, for example, subjected to hot working to become a product. Before the steel material is subjected to hot working, the steel material is heated in a heating furnace. In the case where the steel material is carbon steel, the heating temperature is sometimes around 1150 to 1300°C. In the heating furnace, the steel material is heated at the above high temperature for a long time. The heating furnace is usually an oxidizing atmosphere. Therefore, at the time of heating, oxygen in the furnace atmosphere reacts with Fe of the surface layer of the steel material, and scales are formed. Oxygen in the furnace atmosphere further reacts with carbon of the surface layer of the steel material. In this case, a decarburized layer is formed in the surface layer of the steel material. The decarburized layer reduces the strength of the surface layer of the steel material. Therefore, it is preferable that the decarburization of the steel material be suppressed even if heating at a high temperature is performed.
[0003] In Japanese Patent Application Publication No. H8-53709 (Patent Literature 1) and Japanese Patent Application Publication No. H5-86415 (Patent Literature 2), a technology for suppressing the decarburization of the surface layer of the steel material at the time of heating is proposed.
[0004] The decarburization-preventing material disclosed in Patent Literature 1 takes, as an effective component, a mixture of 100 parts by weight of a glass frit having a softening temperature of 1000°C or higher and 1350°C or lower and 0.5 to 100 parts by weight of a powder of a metal having a melting point of 600°C or higher, and disperses them in water or / organic solvent. In Patent Literature 1, it is described that, after the above decarburization-preventing agent is coated on the surface of the steel material, by heating the steel material, the decarburization of the steel material is suppressed.
[0005] The composition for preventing oxidative decarburization disclosed in Patent Literature 2 contains a fluxing agent component having a softening point or a melting point of 1300°C or lower at 5 to 90% by weight, SiC at 5 to 90% by weight, Cr2O3 at 5 to 60% by weight, and a refractory filler having a melting point of 1300°C or higher at 0 to 75% by weight. In Patent Literature 2, it is described that, after the above composition for preventing oxidative decarburization is coated on the surface of the steel material, by heating the steel material, the oxidation and decarburization of the surface of the steel material are suppressed.
[0006] PRIOR ART DOCUMENTS
[0007] PATENT LITERATURE
[0008] Patent Literature 1: Japanese Patent Application Publication No. H8-53709
[0009] Patent Literature 2: Japanese Patent Application Publication No. H5-86415 SUMMARY
[0010] PROBLEMS TO BE SOLVED BY THE INVENTION
[0011] However, other means besides those described in Patent Documents 1 and 2 can also be used to suppress decarburization of steel when heated at high temperatures of 1150–1300°C.
[0012] The purpose of this disclosure is to provide a coating agent that can suppress decarburization of the steel surface even when the steel is heated at high temperatures, and a method for manufacturing steel using the coating agent.
[0013] Solution for solving the problem
[0014] The coating agent disclosed herein contains glass frit. In terms of mass percentage converted to oxides, the glass frit contains SiO2: 60.0–70.0%, Al2O3: 10.0–24.0%, Na2O: more than 10.0% and less than 20.0%, K2O: 0–5.0%, CaO: 0–6.0%, and MgO: 0–5.0%.
[0015] The steel manufacturing method disclosed herein includes the following steps: applying the coating agent of this disclosure to the surface of the steel; and heating the steel coated with the coating agent at 1150 to 1300°C.
[0016] The effects of the invention
[0017] The coating agent disclosed herein can inhibit decarburization of the steel surface even when the steel is heated at high temperatures. The steel manufacturing method disclosed herein can produce steel in which decarburization is inhibited. Attached Figure Description
[0018] Figure 1 This is a schematic diagram of the EPMA spectrum used to illustrate the method for determining the C concentration ratio ΔC in the embodiments. Detailed Implementation
[0019] The inventors first investigated and researched coating agents that could suppress decarburization of the steel surface even when the steel was heated at high temperatures of 1150–1300°C in a heating furnace. In this specification, high temperature refers to the temperature range of 1150–1300°C.
[0020] When steel is heated at high temperatures in a furnace with an oxidizing atmosphere, decarburization occurs on the steel surface for the following reasons: The oxygen in the oxidizing atmosphere of the furnace comes into contact with the surface of the steel being heated at high temperatures. At this time, the carbon (C) on the steel surface reacts with the oxygen in contact with the steel surface to produce CO gas. The carbon in the steel surface escapes from the surface as CO gas, thus causing decarburization of the steel surface.
[0021] CO gas is also used as a carburizing gas in the carburizing process. Therefore, if CO gas comes into contact with the steel surface, the carbon atoms in the CO gas penetrate the steel surface, and the steel surface is carburized. However, the CO gas generated due to decarburization of the steel surface detaches from the steel surface and diffuses into the oxidizing atmosphere inside the heating furnace.
[0022] Here, the inventors believe that if the CO gas generated from decarburization can be used for carburizing the surface of steel, decarburization of the steel surface can be suppressed. If the CO gas generated from decarburization can be prevented from dispersing into an oxidizing atmosphere and the CO gas can be retained on the steel surface, then the carburization of the steel surface can be carried out using this CO gas. As a result, it is believed that decarburization of the steel surface can be suppressed. As a specific means of suppressing the dispersal of CO gas into an oxidizing atmosphere, if a coating that suppresses the dispersal of CO gas during high-temperature heating can be formed on the steel surface, the CO gas can be retained on the steel surface. Hereinafter, the coating that suppresses the dispersal of CO gas will also be referred to as a "CO gas dispersal suppression film".
[0023] Based on the above investigation, the inventors studied the composition of a coating agent capable of forming a CO gas dispersion suppression film upon high-temperature heating. If the coating agent contains components that vitrify the steel surface upon high-temperature heating, it is possible to form a CO gas dispersion suppression film. The inventors believe that using glass frit as a coating agent that vitrifies at high temperatures is effective. Therefore, the inventors further investigated the composition of the glass frit.
[0024] By appropriately adjusting the contents of SiO2 and Al2O3 (components that raise the softening point) and Na2O, K2O, CaO, and MgO (components that lower the softening point) in the glass frit, a glass coating that fully wets and spreads on the steel surface and can adequately cover the steel surface can be formed at high temperatures. Therefore, the inventors adjusted the contents of the aforementioned components and investigated the relationship between the contents of these components and the decarburization inhibition effect on the steel surface during high-temperature heating. As a result, the inventors obtained the following new insights.
[0025] In glass frits, when the content of K₂O, CaO, and MgO, which are components that lower the softening point, is increased, the oxide scale (iron oxide scale) on the steel surface sometimes reacts with K₂O, CaO, and MgO. In this case, part of the oxide scale is destroyed, and decarburization is promoted in the destroyed part. On the other hand, Na₂O, which is also a component that lowers the softening point, does not readily react with the oxide scale on the steel surface. Therefore, in glass frits, if the content of Na₂O, a component that lowers the softening point, is increased, the oxide scale on the steel surface is more easily maintained and not destroyed during high-temperature heating. In this case, decarburization of the steel is suppressed.
[0026] Based on the above insights, the inventors further investigated the appropriate contents of SiO2, Al2O3, Na2O, K2O, CaO, and MgO in the glass frit used in the coating agent. The results showed that if the glass frit, converted to oxides by mass%, contains SiO2: 60.0–70.0%, Al2O3: 10.0–24.0%, Na2O: more than 10.0% but less than 20.0%, K2O: 0–5.0%, CaO: 0–6.0%, and MgO: 0–5.0%, then decarburization of the steel surface can be sufficiently suppressed during high-temperature heating.
[0027] Based on the above insights, the coating agent of this embodiment and the manufacturing method of the steel using it are described below.
[0028] The coating agent of the first method contains glass frit. In terms of mass percentage converted to oxides, the glass frit contains SiO2: 60.0–70.0%, Al2O3: 10.0–24.0%, Na2O: more than 10.0% but less than 20.0%, K2O: 0–5.0%, CaO: 0–6.0%, and MgO: 0–5.0%.
[0029] The coating agent of the second method is the same as that of the first method, and the glass material satisfies formula (1).
[0030] 0.40≤([K2O]+[CaO]+[MgO]) / [Na2O]≤1.20 (1)
[0031] Here, in equation (1), the K2O content in the glass material, expressed as a percentage of mass when converted to oxides, is substituted for [K2O], the CaO content in the glass material, expressed as a percentage of mass when converted to oxides, is substituted for [CaO], the MgO content in the glass material, expressed as a percentage of mass when converted to oxides, is substituted for [MgO], and the Na2O content in the glass material, expressed as a percentage of mass when converted to oxides, is substituted for [Na2O].
[0032] The coating agent of the third method is the same as that of the first or second method, and also contains carbon powder. For this coating agent, the ratio of the mass (g) of carbon powder to the mass (g) of glass frit in the coating agent is 0.10 to 0.30.
[0033] The fourth method for manufacturing steel comprises the following steps: applying a coating agent as described in any one of the first to third methods to the surface of the steel; and heating the steel coated with the coating agent at 1150 to 1300°C.
[0034] The coating agent of this embodiment and the manufacturing method of steel using the coating agent will be described below.
[0035] [About coating agents]
[0036] The coating agent in this embodiment contains glass frit. Glass frit refers to glass produced by melting glass raw materials, solidifying them, and then pulverizing them. Glass frit can be, for example, granular or flake-shaped.
[0037] [Regarding the composition of the glass material]
[0038] The coating agent of this embodiment contains the following glass frits, expressed as oxides by mass: SiO2: 60.0-70.0%, Al2O3: 10.0-24.0%, Na2O: more than 10.0% and less than 20.0%, K2O: 0-5.0%, CaO: 0-6.0%, and MgO: 0-5.0%. Each component will be described below.
[0039] SiO2: 60.0%~70.0%
[0040] During high-temperature heating, silicon dioxide (SiO2), along with other components, forms a CO gas emission suppression film on the steel surface. SiO2 serves as the matrix for this film. The CO gas emission suppression film allows oxygen to permeate. Therefore, oxygen from outside the CO gas emission suppression film invades the interior of the film, specifically between the film and the steel surface. In this case, oxygen reacts with carbon (C) on the steel surface to generate CO gas. On the other hand, CO gas does not easily permeate the CO gas emission suppression film. Therefore, CO gas does not easily diffuse from the film into the oxidizing atmosphere of the furnace. Consequently, CO gas generated from carbon escaping from the steel surface remains between the film and the surface. As a result, carbon escaping from the steel surface re-enters the surface. Thus, decarburization of the steel surface caused by high-temperature heating is suppressed. If the SiO2 content is less than 60.0%, the above effect cannot be fully achieved.
[0041] On the other hand, if the SiO2 content exceeds 70.0%, the softening point of the glass frit becomes too high. In this case, the coating agent is difficult to wet and spread when heated at high temperatures. Therefore, the CO gas dispersion suppression film formed by the coating agent cannot adequately cover the steel surface. As a result, decarburization on the steel surface is not sufficiently suppressed. If the SiO2 content exceeds 70.0%, the raw material for the glass frit, sometimes mixed with other components, may not melt. In this case, glass frit cannot be manufactured. Therefore, the SiO2 content is 60.0% to 70.0%.
[0042] The preferred lower limit for SiO2 content is 62.5%, and more preferably 65.0%.
[0043] The preferred upper limit for SiO2 content is 68.0%, more preferably 66.0%, and even more preferably 65.5%.
[0044] Al2O3: 10.0–24.0%
[0045] Like SiO2, alumina (Al2O3) forms a CO gas emission-inhibiting film on the steel surface during high-temperature heating. Al2O3 further increases the softening point of the glass frit. Therefore, during high-temperature heating, it inhibits the coating agent from dripping from the steel, making it easier for the coating agent to remain on the steel surface. Consequently, the CO gas emission-inhibiting film formed by the coating agent can fully cover the steel surface during high-temperature heating, effectively suppressing decarburization. If the Al2O3 content is less than 10.0%, the above effects cannot be fully achieved.
[0046] On the other hand, if the Al2O3 content exceeds 24.0%, the SiO2 content decreases relative to the Al2O3 content. In this case, the softening point of the glass frit becomes lower, and the coating agent is prone to dripping from the steel surface during high-temperature heating. Furthermore, if the Al2O3 content exceeds 24.0%, the raw material for the glass frit, sometimes mixed with other components, may not melt. In this case, glass frit cannot be manufactured. Therefore, the Al2O3 content is typically between 10.0% and 24.0%.
[0047] The preferred lower limit for Al2O3 content is 12.0%, and more preferably 14.0%.
[0048] The preferred upper limit for Al2O3 content is 23.0%, more preferably 21.0%, and even more preferably 20.0%.
[0049] Na2O: exceeding 10.0% but below 20.0%
[0050] Sodium oxide (Na₂O) lowers the softening point of the glass frit. This, in turn, reduces the viscosity of the coating agent during high-temperature heating. Consequently, the fluidity of the coating agent increases during high-temperature heating. As a result, the CO gas emission suppression film can adequately cover the steel surface. Compared to other alkaline components (K₂O, CaO, and MgO), Na₂O is less likely to react with oxide scale, which is primarily composed of Fe oxides. Therefore, when carbon steel is heated at high temperatures, the destruction of the oxide scale caused by reaction with the oxide scale can be suppressed. As a result, decarburization associated with oxide scale destruction can be suppressed during high-temperature heating. If the Na₂O content is below 10.0%, the above effects cannot be fully achieved. If the Na₂O content is below 10.0%, the raw material for the glass frit, sometimes mixed with other components, may not melt. In this case, glass frit cannot be manufactured.
[0051] On the other hand, if the Na₂O content exceeds 20.0%, the softening point of the glass frit decreases excessively. Consequently, during high-temperature heating, the viscosity of the coating agent decreases excessively. In this case, during high-temperature heating, the coating agent drips from the steel surface. As a result, the CO gas emission suppression film cannot adequately cover the steel surface, and the steel surface will decarburize. Therefore, the Na₂O content should be between 10.0% and 20.0%.
[0052] The preferred lower limit for Na2O content is 11.0%, and more preferably 12.0%.
[0053] The preferred upper limit for Na2O content is 18.0%, more preferably 16.0%, and even more preferably 14.0%.
[0054] K2O: 0~5.0%
[0055] It may also be free of potassium oxide (K2O). That is, K2O can be any component, and the K2O content can be 0%.
[0056] When K2O is present, it lowers the softening point of the glass frit. Therefore, during high-temperature heating, the coating agent wets and spreads, effectively covering the steel surface. Even a small amount of K2O is sufficient to achieve these effects to some extent.
[0057] However, compared to Na₂O, K₂O reacts more readily with oxide scale, which is primarily composed of Fe oxides. Therefore, if the K₂O content exceeds 5.0%, it will react with the oxide scale during high-temperature heating, easily damaging it. Thus, the K₂O content should be between 0% and 5.0%.
[0058] The preferred lower limit for K2O content is 0.1%, and more preferably 0.5%.
[0059] The preferred upper limit for K2O content is 4.0%, and more preferably 3.0%.
[0060] CaO: 0–6.0%
[0061] It may also be free of calcium oxide (CaO). That is, CaO can be any component, and the CaO content can be 0%.
[0062] When present, CaO lowers the softening point of the glass frit. Therefore, during high-temperature heating, the coating agent wets and spreads, effectively covering the steel surface. Even a small amount of CaO is sufficient to achieve these effects to some extent.
[0063] However, compared to Na₂O, CaO reacts more readily with oxide scale, which is primarily composed of Fe oxides. Therefore, if the CaO content exceeds 6.0%, it will react with the oxide scale during high-temperature heating, easily damaging the oxide scale.
[0064] CaO further promotes the diffusion of oxygen into CO gas, inhibiting the permeation of the CO gas diffusion inhibition film. As mentioned above, the carbon on the steel surface reacts with oxygen in contact with the steel surface to generate CO gas. However, if excessive oxygen in the oxidizing atmosphere of the furnace permeates through the CO gas diffusion inhibition film during high-temperature heating, the generated CO gas further reacts with oxygen to become CO2 gas. CO2 gas does not contribute to carburization of the steel surface; therefore, if the CO gas content decreases due to CO2 gas generation, decarburization of the steel cannot be adequately inhibited. If the CaO content exceeds 6.0%, excessive CO2 gas is generated. Therefore, the CaO content should be between 0% and 6.0%.
[0065] The preferred lower limit for CaO content is 0.1%, and more preferably 0.3%.
[0066] The preferred upper limit for CaO content is 5.5%, more preferably 5.0%, more preferably 4.5%, and more preferably 4.0%.
[0067] MgO: 0–5.0%
[0068] It may also be free of magnesium oxide (MgO). That is, MgO can be any component, and the MgO content can be 0%.
[0069] When MgO is present, it lowers the softening point of the glass frit. Therefore, if MgO is present, the coating agent wets and spreads during heating at high temperatures, effectively covering the steel surface. Even a small amount of MgO is sufficient to achieve the aforementioned effect.
[0070] However, compared to Na₂O, MgO reacts more readily with oxide scale, which is mainly composed of Fe oxides. Therefore, if the MgO content exceeds 5.0%, it will react with the oxide scale during high-temperature heating, easily destroying the oxide scale. Thus, the MgO content should be between 0% and 5.0%.
[0071] The preferred lower limit for MgO content is 0.1%, and more preferably 0.5%.
[0072] The preferred upper limit for MgO content is 4.5%, and more preferably 4.0%.
[0073] The glass frit of this embodiment contains the above-described components. It should be noted that the glass frit may contain 0 to 1.0% impurities (converted to oxides by mass%) as the balance other than the above-described components. These impurities may be introduced during the industrial manufacture of the glass frit from inorganic materials used as raw materials or from the manufacturing environment. Examples of such impurities include Fe₂O₃, B₂O₃, ZrO₂, TiO₂, Sb₂O₃, SrO, BaO, ZnO, PbO, Li₂O, and P₂O₅.
[0074] [Methods for Compositional Analysis of Glass Components]
[0075] The composition of the glass frit was analyzed using the following method. The composition of the glass frit was obtained by performing high-frequency inductively coupled plasma (ICP) analysis on the dried glass frit. Specifically, the contents of elements such as Si, Al, Na, K, Ca, and Mg were determined through ICP analysis. Assuming that all elements form oxides, the oxide contents of each element were calculated from the element contents obtained through ICP analysis. The total content of all oxides obtained through this calculation, set as 100%, was taken as the content (mass %) of each component in the glass frit.
[0076] [Effects of the coating agent in this embodiment]
[0077] The coating agent of this embodiment, containing glass frit with the above-described composition, is applied to the surface of a steel material. When the steel is heated at a high temperature of 1150–1300°C, the coating agent wets and spreads on the steel surface during heating at this high temperature, forming a CO gas emission suppression film. This film retains CO gas, including carbon ions escaping from the steel surface, between the coating agent and the steel surface, inhibiting the emission of CO gas into the oxidizing atmosphere. Therefore, carbon ions escaping from the steel surface re-permeate back to the steel surface. As a result, even when heated at high temperatures, decarburization of the steel surface can be suppressed.
[0078] [Regarding the preferred component ratios in the coating agent]
[0079] Preferably, the coating agent in this embodiment also satisfies the following formula (1).
[0080] 0.40≤([K2O]+[CaO]+[MgO]) / [Na2O]≤1.20 (1)
[0081] Here, in equation (1), the K2O content in the glass material, expressed as a percentage of mass when converted to oxides, is substituted for [K2O], the CaO content in the glass material, expressed as a percentage of mass when converted to oxides, is substituted for [CaO], the MgO content in the glass material, expressed as a percentage of mass when converted to oxides, is substituted for [MgO], and the Na2O content in the glass material, expressed as a percentage of mass when converted to oxides, is substituted for [Na2O].
[0082] As described above, Na₂O, K₂O, CaO, and MgO all lower the softening point of the glass frit and improve the wettability of the coating agent on the steel surface during high-temperature heating. However, during high-temperature heating, K₂O, CaO, and MgO react with the oxide scale (iron oxide scale) formed on the steel surface, partially destroying the oxide scale. Decarburization is promoted in the destroyed oxide scale areas. On the other hand, compared to K₂O, CaO, and MgO, Na₂O is less likely to react with the oxide scale during high-temperature heating. Therefore, in the coating agent of this embodiment, it is preferable to reduce the ratio of K₂O, CaO, and MgO content relative to the Na₂O content.
[0083] Here, compared to K2O, CaO, and MgO, Na2O tends to decrease the viscosity of the coating agent more readily during high-temperature heating. If the Na2O content is excessive compared to the total content of K2O, CaO, and MgO, the viscosity of the coating agent will decrease excessively during high-temperature heating. If the viscosity of the coating agent decreases excessively, it may drip from the steel. If the coating agent drips from the steel, decarburization of the steel surface cannot be suppressed. Therefore, in the coating agent of this embodiment, it is preferable to increase the ratio of the total content of K2O, CaO, and MgO to a certain extent relative to the Na2O content.
[0084] FA is defined as follows.
[0085] FA = ([K₂O] + [CaO] + [MgO]) / [Na₂O]
[0086] FA is an indicator related to scale retention and coating agent viscosity during high-temperature heating. If FA is below 1.20, the reaction between the coating agent and scale is sufficiently suppressed. Therefore, during high-temperature heating, the reaction between the coating agent and scale can be sufficiently suppressed, and the CO gas emission suppression film can adequately cover the steel surface. As a result, decarburization of the steel surface can be further suppressed.
[0087] If the FA value is above 0.40, the viscosity of the coating agent becomes appropriate. Therefore, during high-temperature heating, the coating agent is less likely to drip from the steel. Consequently, the coating agent can fully cover the steel surface, and the CO gas emission suppression film can also fully cover the steel surface. As a result, decarburization of the steel surface can be further suppressed.
[0088] The lower limit of FA is 0.45, the lower limit is 0.55, and the lower limit is 0.65.
[0089] The upper limit for further preferred FA is 1.10, further preferred is 1.00, and further preferred is 0.90.
[0090] [Preferred softening point for glass frit]
[0091] The preferred glass material has a softening point of 900℃ or higher.
[0092] The softening point of the glass frit is determined by its composition. In this embodiment, the glass frit, satisfying the above-mentioned composition, has a softening point of 900°C or higher. If the softening point of the glass frit is 900°C or higher, when the steel is heated at a high temperature, the coating agent wets and spreads on the steel surface, fully covering it. As a result, decarburization of the steel surface is effectively suppressed.
[0093] The preferred lower limit for the softening point of the glass frit is 930°C, and more preferably 950°C. The upper limit for the softening point of the glass frit is not particularly limited, but a preferred upper limit is, for example, 1200°C, more preferably 1100°C, and even more preferably 1000°C.
[0094] [Method for determining softening point]
[0095] The softening point of the coating agent was determined using a thermogravimetric-differential thermal analysis (TG-DTA) apparatus. Specifically, 10 mg of the coating agent was placed in the sample holder of the TG-DTA. The coating agent was heated from room temperature to 1300°C at a heating rate of 10°C / min. The heating atmosphere was Ar. The differential thermal analysis was measured at this point, and the fourth inflection point of the DTA (differential thermal analysis) curve was taken as the softening point of the coating agent.
[0096] [Regarding coating agents containing carbon powder]
[0097] Preferably, the coating agent of this embodiment also contains carbon powder. When the coating agent contains carbon powder, the ratio of the mass (g) of carbon powder to the mass (g) of glass frit is 0.10 to 0.30. These characteristics will be described below.
[0098] [About carbon powder]
[0099] As described above, during high-temperature heating, the coating agent applied to the steel surface melts to form a CO gas emission suppression film. This film covers the steel surface and allows oxygen from the oxidizing atmosphere to permeate through. In cases where the coating agent contains carbon powder, the carbon powder in the CO gas emission suppression film reacts with oxygen to generate CO gas. The generated CO gas remains between the CO gas emission suppression film and the steel surface. Therefore, carburization occurs on the steel surface due to the CO gas.
[0100] As described above, when the coating agent contains carbon powder, heating at high temperature in an oxidizing atmosphere can not only inhibit decarburization of the steel surface, but also enable carburization of the steel surface.
[0101] Carbon powder is a powder composed of carbon. For example, carbon powder may be composed of one or more substances selected from the group consisting of graphite powder, carbon black powder, charcoal powder, bamboo charcoal powder, and coke powder. Preferred carbon powder is graphite powder.
[0102] [Regarding the carbon powder ratio RA]
[0103] The ratio of the mass (g) of carbon powder in a coating agent containing carbon powder to the mass (g) of glass frit is defined as the "carbon powder ratio RA". Preferably, the carbon powder ratio RA is 0.10 to 0.30. Here, the mass (g) of glass frit refers to the mass (g) of glass frit in its dry state, and the mass (g) of carbon powder refers to the mass (g) of carbon powder in its dry state.
[0104] If the carbon powder ratio RA is 0.10 or higher, during high-temperature heating, the carbon in the CO gas dispersion suppression film reacts with oxygen permeating from the outside of the film, generating a sufficient amount of CO gas between the film and the steel surface. This CO gas allows for carburizing of the steel surface. Therefore, when heating at high temperatures in a furnace with an oxidizing atmosphere, decarburization of the steel surface can be further suppressed, and the carbon concentration on the steel surface can be further increased.
[0105] On the other hand, if the carbon powder ratio RA is 0.30 or less, the amount of carbon powder in the coating agent is sufficient relative to the amount of glass frit. In this case, during heating at high temperatures, the CO gas dispersion suppression film can adequately cover the steel surface. Therefore, the carbon powder ratio RA is 0.10 to 0.30.
[0106] The lower limit of the carbon powder ratio RA is further preferred to be 0.11, further preferred to be 0.12, further preferred to be 0.13, further preferred to be 0.14, and further preferred to be 0.15.
[0107] The upper limit of the carbon powder ratio RA is further preferably 0.29, further preferably 0.28, further preferably 0.27, further preferably 0.26, further preferably 0.25, and further preferably 0.24.
[0108] [Method for determining the carbon powder ratio (RA)]
[0109] The carbon powder ratio (RA) in the coating agent was determined by the following method.
[0110] The mass of the coating agent, which changes due to heat, is determined using a thermogravimetric (TG) apparatus. The mass of the coating agent is not particularly limited, for example, 1 g.
[0111] Specifically, the coating agent is heated from room temperature (25°C) to 100°C and maintained at 100°C. The moisture in the coating agent evaporates, and the mass X0 of the coating agent is measured after 30 seconds while maintaining a constant mass. The coating agent after mass measurement is then heated to 600°C and maintained at 600°C. This oxidizes the carbon powder in the coating agent, removing it from the coating agent. After removing the carbon powder from the coating agent, the mass X1 of the coating agent is measured after 30 seconds while maintaining a constant mass. Mass X1 corresponds to the mass of the glass frit. Therefore, mass X0 - mass X1 corresponds to the mass of the carbon powder.
[0112] Using the obtained masses X0 and X1, the carbon powder ratio RA is calculated using the following formula.
[0113] Carbon powder ratio RA=(X0-X1) / X1
[0114] [Regarding the coating agent's components other than glass frit and carbon powder]
[0115] In addition to glass frit and carbon powder, the coating agent of this embodiment may further contain one or more components selected from the group consisting of water, suspending agents, and dispersants. These components may also be omitted. Water, suspending agents, and dispersants will be described below.
[0116] [water]
[0117] When the coating agent is prepared as a slurry, it may contain water, for example. In a slurry-like coating agent, the preferred water content is, for example, 70 to 100 parts by weight relative to 100 parts by weight of glass frit. If the water content is too low or too high, it will be difficult to apply the coating agent to the steel surface. By adjusting the water content, the viscosity of the slurry-like coating agent can be adjusted to a level that allows it to be applied to the steel surface at room temperature.
[0118] [Suspension agent]
[0119] The suspending agent fully disperses the glass frit in the solution (water). The suspending agent may contain, for example, burr clay, and also bentonite and / or sepiolite. In this embodiment, when the coating agent contains burr clay and also bentonite and / or sepiolite, the coating agent is less likely to drip from the steel surface. Furthermore, when the coating agent dries and solidifies, it is less likely to peel off from the steel surface.
[0120] Frog-like clay contains kaolinite-like clay and multiple quartz particles. Specifically, frog-like clay contains kaolinite, halloysite, and quartz.
[0121] Frogeye clay improves the sag resistance of slurry-like coatings. Slurry-like coatings containing frogeye clay are less prone to dripping when applied to steel surfaces at room temperature. Therefore, if frogeye clay is present, the coating can easily cover the entire surface of the steel at room temperature.
[0122] When the coating agent contains crocus clay, the preferred content of crocus clay in the coating agent is 4 parts by mass or more, relative to 100 parts by mass of glass frit. In this case, the coating agent is less likely to drip from the steel surface. A further preferred content of crocus clay is 5 parts by mass or more, and even more preferably 6 parts by mass or more. On the other hand, the upper limit of the preferred crocus clay content is 30 parts by mass. In this case, the glass frit in the coating agent is sufficiently dispersed on the surface of the steel. Therefore, during heating at high temperatures, a CO gas dispersion-inhibiting film is formed more fully.
[0123] Bentonite is a clay with montmorillonite as its main component. Bentonite may also contain silicate minerals such as quartz and opal, silicate minerals such as feldspar and zeolite, carbonate minerals such as dolomite, sulfate minerals, sulfide minerals such as pyrite, etc.
[0124] Sepiolite is a hydrous magnesium silicate, for example, composed of the chemical formula Mg8Si. 12 O 30 It is represented by (OH)4(OH2)4·8H2O.
[0125] Both bentonite and sepiolite inhibit coating agent peeling. Specifically, the coating agent is applied to the steel surface at room temperature. Then, the coating agent is solidified by heating or drying. When the coating agent contains bentonite and / or sepiolite, the bentonite and sepiolite inhibit the peeling of the solidified coating agent from the steel surface. Coating agents containing bentonite and / or sepiolite are not easily peeled from the steel surface even under external force. The coating agent may contain one or more of bentonite and sepiolite.
[0126] Relative to 100 parts by weight of glass, the preferred content of bentonite and / or sepiolite is 4 parts by weight or more. In this case, the peel resistance of the coating agent is further improved. A further preferred content of bentonite and / or sepiolite is 5 parts by weight or more.
[0127] Relative to 100 parts by weight of glass frit, the preferred total content of bentonite and sepiolite is less than 9 parts by weight. In this case, the glass frit is sufficiently dispersed in the coating agent. More preferably, the total content of bentonite and sepiolite is less than 8 parts by weight.
[0128] The suspending agent may contain other clay types besides the aforementioned frog clay, bentonite, and sepiolite. These clay types may contain, for example, iron oxide (Fe2O3).
[0129] [Dispersant]
[0130] The coating agent of this embodiment may also be free of dispersant. When it is contained, the amount of water used to disperse the glass frit and carbon powder can be reduced, resulting in improved adhesion of the coating agent to the steel surface.
[0131] The dispersant is, for example, one or more selected from the group consisting of inorganic salts such as sodium tripolyphosphate, sodium hexametaphosphate, sodium hyperpolyphosphate, acidic sodium hexametaphosphate, sodium borate, sodium carbonate, polymetaphosphate, sodium citrate, sodium tartrate, polyacrylic acid, sodium polyacrylate, sodium sulfonate, polycarboxylate, β-naphthalenesulfonate, melamine sulfonate, and naphthalenesulfonic acid. In the coating agent, the total content of the dispersant is preferably less than 4.5 parts by weight relative to 100 parts by weight of the glass frit.
[0132] [Method for manufacturing coating agent]
[0133] The coating agent of this embodiment is manufactured, for example, by the following method.
[0134] Prepare the components as raw materials for the glass frit that meet the above-mentioned composition. Mix the prepared components. Melt the mixed components. Quickly cool the molten components in water or air to vitrify them. The melting temperature is, for example, 1400–1600°C. Crush the quick-cooled vitrified intermediate. Crushing is, for example, using a ball mill. Through the above steps, the glass frit is manufactured. It should be noted that the softening point of the glass frit can be adjusted to, for example, 900°C or higher by adjusting the composition before mixing. Add, for example, water to the prepared glass frit to produce a slurry-like coating agent.
[0135] When the coating agent contains carbon powder, the carbon powder is further mixed into the above-mentioned slurry-like coating agent. At this time, the amount of carbon powder is adjusted so that the carbon powder ratio RA is 0.10 to 0.30. Through the above manufacturing process, a carbon-containing coating agent is manufactured. Furthermore, as needed, a suspending agent and / or a dispersant are added to the slurry-like coating agent. Through the above process, a coating agent is manufactured.
[0136] [Manufacturing method of steel using coating agent]
[0137] The steel manufacturing method of this embodiment includes the following steps: a step of applying a coating agent to the surface of the steel (coating step); and a step of heating the steel coated with the coating agent at 1150 to 1300°C (heating step). Each step will be described below.
[0138] [Coating Process]
[0139] In the coating process, firstly, the coating agent of this embodiment, manufactured as described in the above-described [method for manufacturing coating agent], is prepared. The prepared slurry-like coating agent is then applied to the steel surface (upper surface, lower surface, and side surface) before heating. For example, the coating agent is applied to the steel surface at room temperature.
[0140] There are no particular limitations on the application method of the coating agent. The operator can apply the coating agent to the surface of the steel using a brush. Alternatively, the coating agent can be applied to the steel surface by spraying or other means. The steel can also be immersed in a bath containing the coating agent (so-called "dipping coating"). These coating methods apply the slurry-like coating agent to the steel surface. Alternatively, the coating agent can be dried after being applied to the steel surface and before the steel is heated at a high temperature.
[0141] There is no particular limitation on the amount of coating agent applied to the steel surface. For example, the amount of coating agent applied to the steel surface is 0.1–0.3 g / cm³. 2 .
[0142] [Steel as the object]
[0143] In the manufacturing method of this embodiment, the type of steel used is not particularly limited. Preferably, the steel used is carbon steel. Here, carbon steel refers to carbon steel for mechanical structures as specified in JIS G 4051:2023 and carbon steel pipes for general mechanical structures as specified in JIS G 3478:2021. When these steels are heated at high temperatures in a furnace with an oxidizing atmosphere, an oxide scale composed of Fe oxides is formed on the surface of the steel.
[0144] [Heating Process]
[0145] The steel coated with a coating agent is heated (heating process). In the heating process, the steel coated with the coating agent is heated at a high temperature of 1150–1300°C. The preferred upper limit of the heating temperature is 1250°C, more preferably 1200°C. The heating time is not particularly limited. The heating time is, for example, 1.0–8.0 hours. The preferred upper limit of the heating time is 5.0 hours, more preferably 2.5 hours.
[0146] The coating agent of this embodiment contains glass frit that satisfies the above-mentioned composition. When heated at a high temperature, the coating agent wets and spreads on the steel surface, forming a CO gas emission suppression film that fully covers the steel surface. This CO gas emission suppression film allows oxygen from the outside to pass through. Between the CO gas emission suppression film and the steel surface, the oxygen that has passed through from the outside combines with carbon ions escaping from the steel surface to generate CO gas. Although the CO gas emission suppression film allows oxygen to pass through, it does not easily allow CO gas to pass through. Therefore, CO gas remains between the CO gas emission suppression film and the steel surface. Through this CO gas, carbon ions escaping from the steel surface re-enter the steel surface. As a result, even when heated at a high temperature of 1150–1300°C, decarburization of the steel surface can be suppressed.
[0147] If the coating agent contains carbon powder and the carbon powder ratio RA is set to 0.10–0.30, then oxygen permeating from the outside reacts with the carbon powder to generate CO gas between the CO gas dispersion suppression film and the steel surface. A sufficient amount of CO gas is generated through the carbon powder. Therefore, by contacting the generated CO gas with the steel surface, not only can decarburization of the steel surface be suppressed, but the carbon concentration of the steel surface can also be increased.
[0148] Example
[0149] The effects of the coating agent according to the embodiments of the present disclosure will be further illustrated in detail below through examples. The conditions in the following examples are one example of conditions used to confirm the feasibility and effectiveness of the coating agent according to the embodiments of the present disclosure. Therefore, the coating agent according to the embodiments of the present disclosure is not limited to this one example of conditions.
[0150] In this embodiment, a coating agent is prepared by mixing various glass frits and graphite powders with different compositions in various mass ratios. Steel coated with the coating agent is heated at a high temperature, and the change in carbon concentration on the surface of the steel before and after heating is investigated. This embodiment will be described below.
[0151] Glass frits (glass frit symbols A to O) as shown in Table 1 were prepared. The composition of the glass frits in Table 1 was determined using the method described in the [Method for Composition Analysis of Glass Frits] above. It should be noted that glass frit symbol H cannot be manufactured because the SiO2 content exceeds the upper limit, making it impossible to melt the mixed components. Similarly, glass frit symbol J cannot be manufactured because the Al2O3 content exceeds the upper limit, making it impossible to melt the mixed components. Furthermore, glass frit symbol K cannot be manufactured because the Na2O content is below the lower limit, making it impossible to melt the mixed components.
[0152] [Table 1]
[0153]
[0154] The glass frits, water, and suspending agents of the glass frit symbols in Table 1 were mixed to prepare the coatings for each test number in Table 2. Each coating was prepared by mixing 70 parts by mass of water, 6 parts by mass of frog-eye clay, and 5 parts by mass of bentonite with 100 parts by mass of glass frit.
[0155] [Table 2]
[0156]
[0157] In tests 5–15, the coating agent further contained carbon powder (graphite powder). The carbon powder ratio RA is shown in Table 2, “Carbon Powder Ratio RA”. It should be noted that the coating agents in tests 1–4 and 16–21 did not contain carbon powder.
[0158] As plate-shaped test pieces, carbon steel equivalent to JIS standard S45C was used. The dimensions of the plate-shaped test pieces were 10 mm thick, 20 mm long, and 20 mm wide. The carbon content of each plate-shaped test piece was 0.45% by mass. Therefore, the carbon concentration [C] on the surface (steel surface) of each plate-shaped test piece was determined. B It is 0.45% by mass.
[0159] The above-mentioned coating agent was applied to the upper surface of the 20×20mm plate-shaped test piece using a brush and then dried. The coating amount for each test number is shown in Table 2. The coating amount was determined by the following method: The mass of the plate-shaped test piece before coating and the overall mass of the test piece after coating were measured separately, and the coating amount was calculated from the difference between the two.
[0160] The coated plate test pieces were heated for 1.0 hour at the heating temperatures (700–1200 °C) listed in Table 2. The atmosphere simulated LNG combustion. Specifically, the atmosphere was adjusted to consist of 2–3% O2, 8–10% CO2, 15–20% H2O, with the balance being N2.
[0161] The C concentration (mass %) on the surface (steel surface) of a heated plate-shaped test piece was determined by the following method.
[0162] A cross-section perpendicular to the length direction (parallel to the width and thickness directions) at the center of the plate-shaped test piece was used as the observation surface. Five measurement points, spaced 1 mm apart in the width direction, were determined on the surface of the plate-shaped test piece at the center of the width direction within the observation surface. These five measurement points were positioned such that the middle measurement point in the row was located at the center of the width direction of the observation surface. Line analysis using an electron probe microanalyzer (EPMA) was performed along a 2000 μm thickness segment from this measurement point. In the EPMA-based line analysis, the accelerating voltage was 15 kV, the irradiation current was 500 nA, the electron beam diameter was 3 μm, and the measurement spacing was 4 μm. The above line analysis was performed on the five measurement segments of the observation surface. At each measurement segment, Fe, O, and C-based spectra were obtained from the surface of the plate-shaped test piece to a thickness of 2000 μm.
[0163] Figure 1 This is a schematic diagram showing the Fe, O, and C-based spectra obtained via EPMA. Figure 1 In the diagram, the horizontal axis represents the distance (μm) from the measurement point on the plate-shaped test piece, i.e., the surface along the thickness direction. Figure 1 In the graph, the vertical axis of the spectra of Fe, O, and C represents their concentrations as a percentage of mass. (Refer to...) Figure 1 The Fe concentration varies from the surface to the thickness D. C Up to this point, there is a downward-convex peak, and the concentration of O decreases from the surface to the thickness D. C Up to this point, there is a convex peak. That is, it can be determined that these Fe and O-based materials have a thickness up to D. C The peaks observed up to the thickness D are caused by the coating agent and oxide film adhering to the surface of the plate-shaped test piece. Therefore, the peaks up to the thickness D are obtained by EPMA based on the Fe, O, and C spectra. C Except for the peaks mentioned above. It should be noted that the thickness D... C Defined as follows.
[0164] In O-based spectroscopy, the concentration of O at which the upward peak caused by the coating agent and oxide coating decreases and reaches its minimum is defined as [O]. S Here, the minimum point is the point where the concentration of O changes from decreasing to increasing; it refers to the location where the first differential is zero. The distance along the thickness direction from the surface to the minimum point is defined as the thickness D. C Then, determine the thickness D. C At a position of 500 μm in the thickness direction, i.e., thickness D RDetermine the thickness D in the spectrum based on carbon (C). C To thickness D R The arithmetic mean of the C concentrations up to this point. It should be noted that, referring to... Figure 1 The extremely low and sharp C concentration peaks, such as peak LP, are attributed to impurities. Therefore, peak LP is based on the thickness D... C To thickness D R The C concentration in the spectrum up to this point is excluded from the arithmetic mean. Peak LP is determined using the following method.
[0165] Let the concentration C at the moment when the peak decay begins be set as concentration C[C]. S Let the concentration C at the moment when the peak decay ends be set as concentration C[C]. M Peaks with a peak attenuation rate (%) of 30% or higher, calculated using the following formula, are identified as peaks LP and excluded from the arithmetic mean of C concentrations.
[0166] Peak attenuation rate = ([C]) S -[C] M ) / [C] S ×100
[0167] The thickness D is obtained from 5 measurement lines using EPMA. C To thickness D R The arithmetic mean of the C concentrations up to this point is defined as the C concentration [C] on the surface of the heated steel. A (quality%).
[0168] Based on the obtained C concentration [C] A The carbon concentration [C] on the surface (steel surface) of the plate-shaped test piece before heating. B The concentration ratio ΔC can be calculated using the following formula.
[0169] ΔC = C concentration [C] A / C concentration [C] B
[0170] The obtained C concentration ratio ΔC is shown in the "ΔC" column of Table 2.
[0171] [Experimental Results]
[0172] Referring to Tables 1 and 2, the coating agents for tests 1 to 8 meet the ranges of each component of the glass frit. Therefore, for the coating agents of these embodiments, the C concentration ratio ΔC is 1.00 or higher, which can suppress decarburization of the steel surface during heating at high temperatures.
[0173] In particular, the coating agents in tests 7 and 8 had an FA of 0.40 or higher and 1.20 or lower, and a carbon powder ratio RA of 0.10 to 0.30. Therefore, in these embodiments, compared with the coating agents in tests 1 to 5, the C concentration ratio ΔC was increased, resulting in excellent decarburization inhibition effect on the steel surface when heated at high temperatures. Furthermore, the coating agent in test 6 also had an FA of 0.40 or higher and 1.20 or lower, and a carbon powder ratio RA of 0.10 to 0.30. Therefore, compared with test 5, which had the same manufacturing conditions as the coating agent in test 6, the C concentration ratio ΔC was increased, resulting in excellent decarburization inhibition effect on the steel surface when heated at high temperatures. The coating agents in tests 1 and 3 had an FA of 0.40 or higher and 1.20 or lower. Therefore, in these embodiments, compared with the coating agents in tests 2 and 4, the C concentration ratio ΔC was increased, resulting in excellent decarburization inhibition effect on the steel surface when heated at high temperatures.
[0174] On the other hand, for the coating agent in test number 9, among the components of the glass frit, SiO2 was below the lower limit, Na2O was below the lower limit, K2O exceeded the upper limit, and CaO exceeded the upper limit. Therefore, the C concentration ratio ΔC was below 1.00, and it could not suppress decarburization of the steel surface during high-temperature heating.
[0175] For the coating agent in test number 10, the Na₂O content in the glass frit was below the lower limit, while the CaO content exceeded the upper limit. Therefore, the C concentration ratio ΔC was below 1.00, and it could not inhibit decarburization of the steel surface during high-temperature heating.
[0176] For tests 11-15, the heating temperature of the plate-shaped test pieces after coating was below 1150℃. Therefore, the C concentration ratio ΔC was below 1.00, and decarburization of the steel surface could not be suppressed during high-temperature heating.
[0177] For the coating agent in test number 16, the SiO2 content in each component of the glass frit was below the lower limit. Therefore, the C concentration ratio ΔC was below 1.00, and it could not suppress decarburization of the steel surface during high-temperature heating.
[0178] For the coating agent in test number 17, the Al2O3 content in each component of the glass frit was below the lower limit. Therefore, the C concentration ratio ΔC was below 1.00, and it could not inhibit decarburization of the steel surface during high-temperature heating.
[0179] For the coating agent in test number 18, the Na₂O content in each component of the glass frit exceeded the upper limit. Therefore, the C concentration ratio ΔC was less than 1.00, and it could not suppress decarburization of the steel surface during high-temperature heating.
[0180] For the coating agent in test number 19, the K2O content in each component of the glass frit exceeded the upper limit. Therefore, the C concentration ratio ΔC was less than 1.00, and it could not inhibit decarburization of the steel surface during high-temperature heating.
[0181] For the coating agent in test number 20, the CaO content in each component of the glass frit exceeded the upper limit. Therefore, the C concentration ratio ΔC was less than 1.00, and it could not suppress decarburization of the steel surface during high-temperature heating.
[0182] For the coating agent in test number 21, the MgO content in the glass frit exceeded the upper limit. Therefore, the C concentration ratio ΔC was less than 1.00, and it could not suppress decarburization of the steel surface during high-temperature heating.
[0183] The embodiments of this disclosure have been described above. However, the above embodiments are merely illustrative examples for implementing this disclosure. Therefore, this disclosure is not limited to the above embodiments, and appropriate modifications can be made to the above embodiments without departing from its spirit.
Claims
1. A coating agent containing glass frit, The glass frit contains, by mass percent when converted to oxides: SiO2: 60.0%~70.0% Al2O3: 10.0–24.0% Na2O: exceeding 10.0% but below 20.0% K2O: 0-5.0% CaO: 0–6.0%, and MgO: 0–5.0%.
2. The coating agent according to claim 1, wherein, The glass material satisfies equation (1): 0.40≤([K2O]+[CaO]+[MgO]) / [Na2O]≤1.20 (1) Here, in equation (1), [K2O] is replaced with the K2O content in the glass material, expressed as a percentage of mass when converted to oxides; [CaO] is replaced with the CaO content in the glass material, expressed as a percentage of mass when converted to oxides; [MgO] is replaced with the MgO content in the glass material, expressed as a percentage of mass when converted to oxides; and [Na2O] is replaced with the Na2O content in the glass material, expressed as a percentage of mass when converted to oxides.
3. The coating agent according to claim 1 or claim 2, further comprising carbon powder, The mass ratio of the carbon powder in the coating agent to the mass of the glass frit is 0.10 to 0.30, wherein the mass of the carbon powder and the mass of the glass frit are expressed in grams.
4. A method for manufacturing steel, comprising the following steps: The process of applying the coating agent according to claim 1 to the surface of steel; and The process of heating the steel coated with the coating agent at 1150-1300°C.
Citation Information
Patent Citations
Composition for preventing oxidation and carburizing of steel material
JP1993086415A
Decarburizing preventive on surface of steel
JP1996053709A
